Implications of the Constructivism Philosophy Perspective in Mathematics Learning - Hendrayanto, Dhani Nur (Journal of Mathematics and Mathematics Education, 2019)
Implication has the aim of comparing the results of research between the past and those that have just been carried out. Basically, the implication of a theory can be defined as a direct result or a consequence of the findings of a research process. Thus various theories of research results emerged. This Constructivism learning theory has a strong influence in the world of education. As a result, the learning orientation in the classroom has shifted. Learning orientation shifted from teacher-centered teaching to student-centered learning. Students are no longer positioned as empty vessels ready to be filled. With a resigned attitude students are prepared to be filled with information by their teachers. Or students are conditioned in such a way to receive knowledge from their teachers. Now the teacher learning partners are students. Teachers are not the only information center or learning center. Meanwhile other learning sources can be peers, nature, the internet and others.